In-vivo measurement of tri-axial loading at the head during the rugby tackle - Jones, R.; Greig, M. (Research in Sports Medicine, 2017)
To investigate the anatomical distribution of linear and rotational forces during the tackle scenario, male rugby players performed a total of 48 trials, as ball carrier or tackler. Participants wore headgear accommodating three global positioning system units measuring uniaxial acceleration at the occipital region (OR), left tempero-parietal (LT-PR) and right tempero-parietal region (RT-PR). An additional unit was located at the cervico-thoracic spinal region in a custom vest. There was a significant main effect for tackle condition (P < 0.001), with the tackler exposed to significantly greater load than the ball carrier, supporting epidemiological observations. A repeated measure general linear model also revealed a significant (P < 0.001) main effect for unit location upon 3D load, with significantly higher load at the CSR (1.63 ± 0.54 a.u.) and OR (1.67 ± 0.94 a.u.) units when compared to the LT-PR (1.23 ± 0.39 a.u.) and RT-PR (1.21 ± 0.44 a.u.) units. The anatomical specificity in loading supports epidemiological observations and provides an insight into potential concussion aetiology.